Liquefaction and performance of foundation systems in Iskenderun during 2023 Kahramanmaras-Turkiye earthquake sequence - Ozener, Pelin; Monkul, M. Murat; Bayat, Ece Eseller; Ari, Abdulmuttalip; Cetin, Kemal Onder (ELSEVIER SCI LTD, 2024)
On February 6, 2023, two devastating earthquakes occurred on the East Anatolian Fault, Turkiye. The earthquakes had severe impacts on civil engineering structures in Iskenderun, Hatay. Reconnaissance studies were performed in Iskenderun to document and evaluate the performances of the different foundation systems and improved ground. Several soil liquefaction cases, including a boulevard, a mosque complex, fishing shelter, and military quarters were observed and documented along with the ground conditions and surface ejecta characteristics. The site observations during the reconnaissance study showed that the application of the unreinforced concrete piles was not a proper foundation solution against seismic loading and did not perform well. Whereas foundation systems including reinforced barrette piles and improved sites with jet grout columns were observed to perform quite well with negligible/no deformations. Observations at several structures indicate that conventional pile foundations also performed well, however structures built on deep foundation systems together with prior jet grout improved sites performed notably better.
Keywords: Liquefaction; Deep foundations; Earthquake; Sand; Silty sand; Ground failure; Jet grout; Ground improvement; Engineering; Geology